Percepção e valoração ambiental de um parque urbano: o caso do parque municipal do Sabiá, Uberlândia-MG - Borges, Ciro Josué Alves (2017)
The current economical model doesn't provide means of calculating the immaterial values of the natural resources, and the valuation of the environmental assets is indispensable for to be created grows up a reference value for these resources, that it will grant a market signaling for the possibility of coining politics of maintainable use. The environmental economical valuation tries to esteem the value certain economical environmental resource through the equivalence the other resources, like as impacts in a certain area of permanent preservation or an urban park, which possess exalt importance for the quality of life of the population and environmental preservation. For those reasons, in this study, an urban park was valued. The urban parks, for their characteristics physical, social and environmental, they are considered appropriate for leisure and scientific studies, besides providing environmental improvements in your circuit. In that way, this study looked for to value, for the method of uncertain valuation, the Park of the Sabiá, in Uberlândia-Minas Gerais, as tool for the preservation of the natural resources in him existent and improvement of the administration and administration of this urban park. For such, it was used a questionnaire that consisted of a group of questions socioeconomic, ecological and of environmental perception, related to the interviewee's profile and their attitudes, including information that subsidized the interpretation of the values of the Disposition to Pay (DTP) and of the Disposition to Receive (DTR) for the preservation of the park. They were applied 350 questionnaires, and the interviewees, 70,28% presented positive DTP, being your medium value of R$14,95 and the annual value of DTP of R$14.792.606,40. The results of DTR presented that 66,57% would not be willing to receive, this way, only 33,43% accepted to receive, and they declared a DTR positive average of monthly R$14,97, in that case, R$14.812.395,84 annual. In the Disposition to Pay the variable that indicates the education level presented that the individuals that possess the third complete degree have larger disposition to pay for the preservation of the park. The increase of the family income indicated that this doesn't interfere in positive DTP. The variable that the interviewee is indicated already heard to speak in sustainability, it demonstrated that a larger probability of the individual exists to present a positive DTP if already has ear to speak in sustainability. Visit's frequency to the park interfered negatively in DTP, showing that the frequency doesn't reach the value of positive DTP directly. Already, in the Disposition to Receive, the variable age presented an indication that the increase of the age generates a positive variation in the value in DTR. The condition of the home indicated that the residents that possess homes in better conditions have larger disposition to receive for the exploration of the resources of the park. In the variable time of home, it can be verified that the time in years that the resident lives at the place doesn't influence in the disposition to pay. The variable importance of the park for preservation of the native vegetation of the Cerrado presented that that science would not influence in DTR. Already, the variable that questions the interviewees are in agreement with the exploration of the park case brought job for the area, it indicated that the interviewees that are in agreement with the exploration of the park present a larger disposition to receive. The main conclusions appear for an environmental conscience, because, the residents of the I spill of the park present positive DTP and DTR negative, what evidences the value social, cultural and environmental of the Park of the Sabiá.